2018
DOI: 10.1002/lary.27405
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative respiratory complications and racial disparities following inpatient pediatric tonsillectomy: A cross‐sectional study

Abstract: Objectives/Hypothesis To study rates of respiratory complications/interventions among inpatient tonsillectomy patients in the United States and identify risk factors for these events. Study Design Retrospective database review. Methods Children (age < 18 years) undergoing tonsillectomy with or without adenoidectomy in 2006, 2009, and 2012 were studied using the Kids Inpatient Database, Healthcare Cost and Utilization Project, Agency for Healthcare Research and Quality. Outcomes were analyzed for respiratory ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 33 publications
4
51
0
1
Order By: Relevance
“…Tonsillectomy is one of the most common procedures in pediatric patients and is a relatively safe procedure 1 ; however, it carries risk, in terms of airway complications with the rate of 2.4%. 2 Although children with risk factors are more likely to experience airway complications after tonsillectomy, 3 upper airway obstruction by the tongue or by uvular edema can occur and may lead to fatal complications even in healthy children without any risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Tonsillectomy is one of the most common procedures in pediatric patients and is a relatively safe procedure 1 ; however, it carries risk, in terms of airway complications with the rate of 2.4%. 2 Although children with risk factors are more likely to experience airway complications after tonsillectomy, 3 upper airway obstruction by the tongue or by uvular edema can occur and may lead to fatal complications even in healthy children without any risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a growing body of literature that suggests that there may be a racial predilection to postoperative respiratory complications, with black children being at higher risk. 14,17 We are unable to assign causality due to the nature of this study, but there were significantly fewer white children and significantly more black and Hispanic children in the inpatient cohort. This again may reflect recognition of higher-risk populations or higher rates of other comorbidities, such as obesity or age \3 years.…”
Section: Discussionmentioning
confidence: 85%
“…Within the ENT surgical population, most studies on racial difference in surgical outcomes have been from single institutions and contained relatively small sample sizes of children undergoing predominantly adenotonsillectomy procedures 15 . In a recent large retrospective report, Kou et al examined 30 617 children undergoing inpatient adenotonsillectomy for either tonsillitis or OSA and found that black children experienced a 1.5 times higher risk than their white counterparts regarding the incidence of respiratory complications including pneumonia, postoperative pulmonary edema, postoperative tracheal intubation, and noninvasive and invasive mechanical ventilation 16 . This effect persisted after adjustment for gender, OSA, obesity, sickle cell anemia, and asthma.…”
Section: Discussionmentioning
confidence: 99%